2022
DOI: 10.3389/fcvm.2022.939297
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Transcatheter pulmonary valve-in-valve implantation in a deteriorated self-expandable valve caused by infective endocarditis

Abstract: BackgroundInfective endocarditis is a complication with high mortality in patients with congenital heart disease, particularly for those with bioprosthetic valve.Case summaryWe report a case of a 54-year-old female with a history of tetralogy of Fallot who had been surgically repaired using a transannular patch due to severe pulmonary insufficiency with right heart enlargement and presented with worsening dyspnea. She had received transcatheter pulmonary valve implantation (TPVI) 5 years ago. Unfortunately, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…The survival rate from endocarditis was estimated as 91% in this study, relatively lower than in previous studies with Harmony valves (100%) 13 . The final occurrence of endocarditis in our study was reported at 5 years after implantation 16 . But a different finding was demonstrated according to the intermediate‐term follow‐up data of the international Venus P‐valve database outside China as no imaging or laboratory evidence of endocarditis were detected 10 .…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The survival rate from endocarditis was estimated as 91% in this study, relatively lower than in previous studies with Harmony valves (100%) 13 . The final occurrence of endocarditis in our study was reported at 5 years after implantation 16 . But a different finding was demonstrated according to the intermediate‐term follow‐up data of the international Venus P‐valve database outside China as no imaging or laboratory evidence of endocarditis were detected 10 .…”
Section: Discussioncontrasting
confidence: 81%
“…13 The final occurrence of endocarditis in our study was reported at 5 years after implantation. 16 But a different finding was demonstrated according to the intermediateterm follow-up data of the international Venus P-valve database outside China as no imaging or laboratory evidence of endocarditis were detected. 10 The high incidence of endocarditis in our study might be attributed to the lack of strict clinical practice in performing antibiotic prophylaxis following surgery and percutaneous procedures, including PPVI, in China.…”
Section: Discussionmentioning
confidence: 97%